(untitled) (Research, Society and Development, 2021)
The main goal of this study is to evaluate the scientific production on the adoption of new technologies to help the marketing field on the promotion of strategies that aim to help brazilian organizations to become more competitive. A quantitative methodology was employed to measure the models used, throughout publications (EnANP AD, EMA and CLA V) from 2010 to2018. The results found were the restriction on the adoption of new technologies to some types of products or services, and the fast evolution of said technologies in the market. It is possible to see that the most utilized models in the analysis were T AM and UT AUT2, which shows the importance of these model’s usage to evaluate the consumption and acceptance from consumers to products offered to them. Only 37 articles were presented in events such as EMA, EnANP AD and CLA V from 2010 to 2018. This subject is contemporary in Brazil, and has limitations that jeopardize deeper studies, but it is emerging and it has a lot of potential for greater studies that approach the theme of new technologies in marketing.